Competitive role of structural properties of titania–silica mixed oxides and a mechanistic study of the photocatalytic degradation of phenol - Rasalingam, Shivatharsiny; Kibombo, Harrison S.; Peng, Rui; Koodali, Ranjit T. (environmental, 2014)
TiO2–SiO2 mixed oxide materials were hydrothermally synthesized and the photocatalytic degradation of phenol under UV-irradiation was evaluated. We also demonstrated that varying the co-solvent, modulates the structural properties of the materials. In particular, the use of non-polar co-solvents such as toluene seemed to increase the crystallinity, surface area, and pore diameter while the crystallite size of titania seemed to change little. A comprehensive characterization using surface and bulk techniques evidenced the role of porosities, crystallinity, and Ti–O–Si linkages of the mixed oxides as significant factors that contribute to the degradation of phenol. The TiO2–SiO2 mixed oxide material prepared using only ethanol as the solvent showed 24% degradation of phenol after 120 min of irradiation whereas other mixed oxide materials degraded phenol more efficiently (57% to 100%) in the same duration of time. The higher photocatalytic activities of the mixed oxide materials prepared using non-polar solvents is attributed to a combination of factors that include higher Apparent Surface Coverages of Ti–O–Si heterolinkages, larger pore sizes, and most importantly higher crystallinities of the titania phase. Larger pore sizes enabled better transport of reactant molecules and products to and from the active sites (Ti–O–Si heterolinkages) and the higher crystallinities of the titania phase helped in minimizing the electron–hole recombination in these photocatalysts, and thus resulted in high degradation efficiencies.
Keywords: Photocatalysts; Titania–silica; Phenol; Heterolinkages; Crystallinity